Changes in healthy Wistar rat gut microbiome by short-term dietary cava lees intervention - Berlanga, Mercedes; Martín-García, Alba; Guerrero, Ricardo; Riu-Aumatell, Montserrat; López-Tamames, Elvira (Frontiers in Nutrition, 2025)
IntroductionThe gut microbiome plays a crucial role in host health through complex host–microbe interactions. Beta-glucans, structural polysaccharides found in yeast cell walls, have emerged as promising modulators of immune function and microbial ecology. Cava lees, a by-product of sparkling wine production composed of Saccharomyces cerevisiae cell walls, represent a rich source of beta-glucans that could be upcycled for nutritional and therapeutic applications.MethodsTwenty-four Wistar rats (12 males, 12 females) were randomly divided into control and treatment groups. The treatment group received daily doses of 2,000 mg lees/kg body weight for 14 days. Shotgun metagenomic analysis was performed to assess microbial composition and functional changes.ResultsA 14-day cava lees supplementation study revealed significant shifts in gut microbiota composition and function. Baseline microbiota was dominated by Bacillota (64–72%) and Bacteroidota (23–32%) with sex-specific differences at the family level. Post-supplementation analysis showed increased Shannon diversity across both sexes, with beneficial enrichment of Bifidobacteriaceae and Rikenellaceae families and reduction of Eubacteriaceae. While global metabolic profiles remained stable, targeted functional pathways were significantly changed, including butyrate production genes. Females exhibited particularly elevated secondary bile acid modification genes (Mann–Whitney-Wilcoxon test p = 0.032), and male oxidative stress response pathways (Mann–Whitney-Wilcoxon test p = 0.016) showing both a potentially sex-dependent responses to dietary intervention.ConclusionWorking with healthy individuals provides a clear understanding of the normal, baseline microbiota composition and function before any intervention. These findings suggest a degree of plasticity of the gut microbiome and its responsiveness to dietary modifications. Beta-glucans from cava lees appear to create a favorable environment for beneficial bacteria, with sex-specific changes of certain bacterial families and functions. These findings provide a foundation for future translational research in humans. Nonetheless, to establish their true impact on human health, these observations in rodent models must be validated through appropriately designed human clinical studies.